2016
DOI: 10.1038/onc.2016.392
|View full text |Cite
|
Sign up to set email alerts
|

Tumors overexpressing RNF168 show altered DNA repair and responses to genotoxic treatments, genomic instability and resistance to proteotoxic stress

Abstract: Chromatin DNA damage response (DDR) is orchestrated by the E3 ubiquitin ligase ring finger protein 168 (RNF168), resulting in ubiquitin-dependent recruitment of DDR factors and tumor suppressors breast cancer 1 (BRCA1) and p53 binding protein 1 (53BP1). This ubiquitin signaling regulates pathway choice for repair of DNA double-strand breaks (DSB), toxic lesions whose frequency increases during tumorigenesis. Recruitment of 53BP1 curbs DNA end resection, thereby limiting homologous recombination (HR) and direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 59 publications
3
32
1
Order By: Relevance
“…Nuclear proteostasis maintenance is fundamental for the preservation of genome integrity (Shibata & Morimoto, 2014 In agreement with the literature, proliferating HeLa cells contained nuclear 53BP1 foci that colocalized with ubiquitinated H2A (H2A-Ub; Fig EV5B; Harrigan et al, 2011). As previously shown by independent groups, we also found that the number of these 53BP1 foci strongly decreased upon proteasome inhibition with MG132, alone or combined with OP-puro ( Fig 7A and B), and this, in turn, correlated with a reduction of H2A-Ub levels and an accumulation of polyUb substrates ( Fig EV5C; Mimnaugh et al , 1997;Jacquemont & Taniguchi, 2007;Mailand et al, 2007;Chroma et al, 2016). The number of 53BP1 foci returned to basal levels when proteasomal activity was restored during the recovery phase, indicating that nuclei recovered their ability to recognize and protect fragile chromosomal sites from erosion (Fig 7A and B).…”
Section: Of 19supporting
confidence: 87%
See 1 more Smart Citation
“…Nuclear proteostasis maintenance is fundamental for the preservation of genome integrity (Shibata & Morimoto, 2014 In agreement with the literature, proliferating HeLa cells contained nuclear 53BP1 foci that colocalized with ubiquitinated H2A (H2A-Ub; Fig EV5B; Harrigan et al, 2011). As previously shown by independent groups, we also found that the number of these 53BP1 foci strongly decreased upon proteasome inhibition with MG132, alone or combined with OP-puro ( Fig 7A and B), and this, in turn, correlated with a reduction of H2A-Ub levels and an accumulation of polyUb substrates ( Fig EV5C; Mimnaugh et al , 1997;Jacquemont & Taniguchi, 2007;Mailand et al, 2007;Chroma et al, 2016). The number of 53BP1 foci returned to basal levels when proteasomal activity was restored during the recovery phase, indicating that nuclei recovered their ability to recognize and protect fragile chromosomal sites from erosion (Fig 7A and B).…”
Section: Of 19supporting
confidence: 87%
“…Our data also identify nuclear protein quality control as a weak link in the proteostasis network, because of the continuous targeting of newly synthesized aberrant proteins to the nucleus for proteasomal degradation. Upon proteasome inhibition, a link between decreased levels of free ubiquitin and defective formation of DNA repair compartments at fragile chromosomal sites was previously reported by independent groups (Mailand et al, 2007;Chroma et al, 2016). Our data identify newly synthesized proteins, including DRiPs, as the main species that upon proteasome inhibition deplete free ubiquitin, thereby compromising DNA damage sensing/repair.…”
Section: Discussionsupporting
confidence: 75%
“…In several DDR process, RNF168 locates at DNA repair sites and promotes mono‐ubiquitination of H2A/H2AX at K13‐15 to drive DNA repair complex formation . Previous studies have shown that RNF168 could participate in chemotherapy resistance in a group of malignancies . In our analysis, the public cancer database shows RNF168 has gene amplification in oesophageal cancer patients, which tends to correlate with poor overall survival.…”
Section: Introductionmentioning
confidence: 65%
“…In several DNA damage process, RNF168 is recruited to DNA damage foci and promotes mono‐ubiquitination of H2A/H2AX at K13‐15 to facilitate the formation of DNA repair complex . Previous studies showed that RNF168 could participate in chemotherapy resistance in various type of cancers . Interestingly, RNF168 is highly amplified in oesophageal cancer patients, which lead our interests to dig into the mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, the above studies reflect the emerging evidence that variable expression of the components of the UPR may have important roles in human cancer. These observations can be paired with emerging preclinical studies indicate that UPR is intricately linked to transformation (16), genomic instability (59), tumorigenesis (60), metastasis (61), dormancy and resistance to anti-cancer therapy (62). Further studies are needed in both spheres to determine the context dependent roles of the UPR in such a manner that measurements of UPR components can one day serve as biomarkers for UPR targeted therapy.…”
Section: Atf6: the Least Well Understood Arm Of The Uprmentioning
confidence: 94%